Characterization of Brucella abortus Soluble Antigen Employed in Immunoassay - Berman, David T. (1980)
A soluble antigen extract of Brucella abortus (BASA) has been prepared by the National Veterinary Services Laboratories and furnished to a number of workers who are examining antibody-mediated and cell-mediated immune responses of cattle infected with B. abortus. Three lots of BASA were examined. There were quantitative but not qualitative differences among lots by content of protein, total carbohydrate, hexose, fatty acid, and 2-keto-3-deoxyoctonic acid. The presence of smooth lipopolysaccharide was demonstrated by the presence of 2-keto-3-deoxyoctonic acid and lipid, by Limulus lysate gelation activity, and by formation of characteristic lipopolysaccharide precipitates in immunoelectrophoresis. A polysaccharide antigen as well as two nonsurface antigens, A2 and C, were also identified. BASA is a satisfactory antigen for use in the enzyme-linked immunosorbent assay since the smooth lipopolysaccharide component bound to polystyrene and functioned in the test. Normal murine spleen cells showed a mitogenic response to BASA similar to that produced by purified smooth lipopolysaccharide. BASA has been used in other laboratories to stimulate peripheral blood leukocytes from cattle infected with B. abortus. Because BASA is a mixture of antigenic components shown to have mitogenic effects in the mouse system, questions on the nature of its stimulatory effect on bovine cells are raised.